Measuring the benefit of 4 years of intravitreal ranibizumab treatment for neovascular age-related macular degeneration. Issue 12 (21st September 2012) - Pushpoth, Sreekumari; Sykakis, Evripidis; Merchant, Kinnar; Browning, Andrew C; Gupta, Rajen; Talks, S James
Abstract : Aim: To analyse the benefit of intravitreal ranibizumab over 4 years for patients with neovascular age-related macular degeneration (AMD). Methods: A retrospective case note review of all patients who started treatment between August 2007 and September 2009 in our unit, minimum follow-up 2 years, maximum 4 years. The main outcome measures were: numbers of patients with different levels of vision, changes in visual acuity, number of treatments and numbers remaining under follow-up. Results: 1086 eyes of 1017 patients received treatment. Numbers of patients remaining under follow-up were 892/1017 (87.71%) at 12 months, 730/1017 (71.78%) at 24 months, 468/730 (64.11%) at 36 months and 110/217 (50.69%) at48 months. The main reasons for patients no longer being under follow-up were the consequences of old age or transfer of care. 50% of patients had 6/18 or better over 4 years. Patients received on average 5.79±2.53, 9.15±3.79, 11.22±4.92 and 13.7±7.84 injections by 12, 24, 36 and 48 months, respectively. Conclusions: We suggest that the numbers of patients with a particular level of vision may best reflect the actual benefit of AMD treatment provided by a service. Long-term follow-up is required as only 72/730 (10%) had been discharged at 36 months, half of whom had good vision of greater than 60 letters. 83% and 65% of patients needed treatment in the third and fourth year. Follow-up may be for the rest of the patients' life or at some point they may no longer be well enough to attend.